Optimalisasi Pelayanan Dan Motivasi Kerja Dengan Kedisiplinan Pegawai Dalam Mengukur Kepuasan Kinerja - Amir; Jafar Haruna; Mursalim (BEduManagers Journal : Borneo Educational Management and Research Journal, 2021)
The Influence Sevice Optiamisation and Job Motivation with Employee Dicipliner in Measure Job Satisfaction Toward Administration Power at UPT and Education Official East Kutai Regency Provincy East Kalimantan. There is research to aim for the service optimalisation effect and employee motivation with employee dicipliner in measure work satisfaction toward administration power at UPT and Education Official East Kutai Rigrncy. There is kausal study do it Eighteen District and twenty UPT between one Education Official East Kutai Regency. The method used in this Research is Quantitative method with multiple Regression Analisis. The Sample of this research is one hundred and two respondent of four hundred fifty nine at Population. The result of this research is that there is a significant positive influence either partially or colletively between the effect service optimalisation and work motivation with employee dicipliner to measure work satisfaction employees toward administration power at UPT and Education Official East Kutai Regency. Based on the results of this study the researcher concludes that the batter of service optimalisation and work motivation with employee to dicipliner to result in more the more feeling satisfaction in the job.(1), The Higght more the more in motivation work or duty do it to result in of satisfaction the work (2), The Dicipline more the more and rule obdient employee doing the duty or manner rule, more the more to hoist satisfaction work (3), More the more service optimalisation, more the more work motivation with more the more rule obdient employees in dicipline their work becoming satisfaction to gether the administration power, more the more to services.